2004
DOI: 10.1080/08037050310031035
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system and microvascular alterations in normotensives with a family history of hypertension

Abstract: Autonomic nervous system and microvascular alterations at pre-hypertensive stage of hypertension have still not been fully elucidated. We aimed at addressing central and local influences on microvascular reactivity at pre-hypertensive stage of hypertension. To that end, we studied microvascular reactivity in 59 normotensives with a family history of hypertension and 46 controls. We measured laser-Doppler flow on the finger nailfold skin in the resting condition, after an 8-min occlusion of digital arteries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
2
17
0
2
Order By: Relevance
“…Conclusions: Our findings suggest that persistent JS lowers HRV time-domain parameters, supporting the hypothesis that the ANS disorders may play an intermediate role in the relationship between work stress and CVD. tone in the offspring of hypertensive patients compared to those without a family story of hypertension, and Mavel et al [23] have reported similar findings in normotensive subjects with family story of hypertension. A reduction in HRV was also reported among healthy subjects with positive family history of diabetes [24,25] or premature heart attack and sudden death [26].…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Conclusions: Our findings suggest that persistent JS lowers HRV time-domain parameters, supporting the hypothesis that the ANS disorders may play an intermediate role in the relationship between work stress and CVD. tone in the offspring of hypertensive patients compared to those without a family story of hypertension, and Mavel et al [23] have reported similar findings in normotensive subjects with family story of hypertension. A reduction in HRV was also reported among healthy subjects with positive family history of diabetes [24,25] or premature heart attack and sudden death [26].…”
supporting
confidence: 61%
“…A study in 159 female nurses evidenced lack of association between job strain and HRV on working and on resting days [21], but the authors reported rMSSD only as a measure of time-domain HRV. Clays in a large-scale study of white and studies have shown that these people are more prone to have lower vagal tone and HRV decrements [22][23][24][25][26]. Secondly, we carefully selected participants excluding the subjects with disorders of the cardiovascular system, neuroendocrine and psychological or pharmacological treatments, which are known to have effects on the autonomic nervous system, and if not selectively associated with the exposure their inclusion might have contributed to get null results in terms of association between exposure and outcome.…”
Section: Strengths Of the Studymentioning
confidence: 99%
“…In recent years, associations have been found between cardiac vagal tone (as reflected by respiratory sinus arrhythmia (RSA) and other indices) and several physiologic processes, including congestive heart failure (Saul et al, 1988), diabetes (Lindmark et al, 2003), hypertension (Maver et al, 2004), and weight gain (Arrone et al, 1995). In addition, reliable individual differences in cardiac vagal tone have been established as have aging-associated reductions in vagal tone (Craft and Schwartz, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In persons suffering from family history of arterial hypertension the changes in reactivity of central derived microcirculation, which resulted from altered sympathetic -vagal balance, accompanied by decreasing of parasympathetic activity [1,2], were observed. Similar results was obtained in previous own researches on persons suffering from arterial hypertension [3].…”
Section: Discussionmentioning
confidence: 99%